The molecular mechanism underlying Roberts syndrome involves loss of ESCO2 acetyltransferase activity (2008)
Roberts syndrome/SC phocomelia (RBS) is an autosomal recessive disorder with growth retardation, craniofacial abnormalities and limb reduction. Cellular alterations in RBS include lack of cohesion at the heterochromatic regions around centromeres and the long arm of the Y chromosome, reduced growth capacity, and hypersensitivity to DNA damaging agents. RBS is caused by mutations in ESCO2, which encodes a protein belonging to the highly conserved Eco1/Ctf7 family of acetyltransferases that is involved in regulating sister chromatid cohesion. We identified 10 new mutations expanding the number to 26 known ESCO2 mutations. We observed that these mutations result in complete or partial loss of the acetyltransferase domain except for the only missense mutation that occurs in this domain (c.1615T>G, W539G). To investigate the mechanism underlying RBS, we analyzed ESCO2 mutations for their effect on enzymatic activity and cellular phenotype. We found that ESCO2 W539G results in loss of autoacetyltransferase activity. The cellular phenotype produced by this mutation causes cohesion defects, proliferation capacity reduction and mitomycin C sensitivity equivalent to those produced by frameshift and nonsense mutations associated with decreased levels of mRNA and absence of protein. We found decreased proliferation capacity in RBS cell lines associated with cell death, but not with increased cell cycle duration, which could be a factor in the development of phocomelia and cleft palate in RBS. In summary, we provide the first evidence that loss of acetyltransferase activity contributes to the pathogenesis of RBS, underscoring the essential role of the enzymatic activity of the Eco1p family of proteins.